2022
DOI: 10.3389/fpubh.2022.1050471
|View full text |Cite
|
Sign up to set email alerts
|

An exercise prescription for patients with lung cancer improves the quality of life, depression, and anxiety

Abstract: IntroductionLung cancer has the highest rates of morbidity and mortality among all cancers. Patients with lung cancer inevitably confront psychosocial discomforts and progressively experience depression and anxiety that potentially impact the clinical outcomes [e.g., quality of life (QoL)]. These mental disorders in patients with lung cancer may effectively be alleviated with prescribed Chinese traditional mind-body exercises. This study aimed to determine the effect of the exercise prescription containing Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…A higher frequency of running and walking was reported to reduce the risk of death from respiratory disease, pneumonia, and aspiration pneumonia in a dose-dependent manner [14]. Furthermore, studies on patients with COPD or lung cancer have reported bene cial effects of exercise or physical activity on the clinical course of the disease [9,17]. These results are consistent with our ndings showing that physical activity is bene cial to the prognosis of respiratory diseases; however, our results also differed, as the previous studies recruited walkers or patients with speci c diseases were targeted.…”
Section: Discussionmentioning
confidence: 99%
“…A higher frequency of running and walking was reported to reduce the risk of death from respiratory disease, pneumonia, and aspiration pneumonia in a dose-dependent manner [14]. Furthermore, studies on patients with COPD or lung cancer have reported bene cial effects of exercise or physical activity on the clinical course of the disease [9,17]. These results are consistent with our ndings showing that physical activity is bene cial to the prognosis of respiratory diseases; however, our results also differed, as the previous studies recruited walkers or patients with speci c diseases were targeted.…”
Section: Discussionmentioning
confidence: 99%
“…The other analyses showed that impaired pulmonary function was an independent risk factor of death from cardiac and respiratory diseases 3 . Several studies have reported that physical activity, such as walking, has been shown to reduce the risk of respiratory disease 9 , 10 , 14 , 17 . A higher frequency of running and walking was reported to reduce the risk of death from respiratory disease, pneumonia, and aspiration pneumonia in a dose-dependent manner 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A higher frequency of running and walking was reported to reduce the risk of death from respiratory disease, pneumonia, and aspiration pneumonia in a dose-dependent manner 14 . Furthermore, studies on patients with COPD or lung cancer have reported beneficial effects of exercise or physical activity on the clinical course of the disease 9 , 17 . These results are consistent with our findings showing that physical activity is beneficial to the prognosis of respiratory diseases; however, our results also differed, as the previous studies recruited walkers or patients with specific diseases were targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression evaluation[ 25 ]: Self-rating anxiety scale (SAS) was used to assess the patient's anxiety before and after nursing care. The scale contains five positive questions and 15 negative questions, and the score was the sum of the scores on a scale of 1 to 44, with 50-59 for mild anxiety, 60-69 for moderate anxiety, and ≥ 70 for severe anxiety.…”
Section: Methodsmentioning
confidence: 99%